The Role of Women’s Leadership In Islamic Elementary Schools: A Gender Perspective Study - Aang Kunaepi; Yusuf Isnan; Nasikhin Nasikhin; Abdulraya Panaemalae (MUWAZAH : jurnal kajian gender, 2024)
This study examines the supporting and inhibiting factors of female leadership in Islamic elementary schools. This qualitative study collects data through in-depth interviews, observation, and documentation studies. The collected data was validated using triangulation and member checking, and then analyzed using the Miles and Huberman model. The selection of women to occupy essential positions in schools is based on their competence and experience. Women are given equal rights to develop curriculum managerial potential and abilities. As a result, female teachers increasingly have the same abilities and competencies, even better than men. The nature of women who are gentler, patient, detailed, and thorough is allegedly one of the reasons why leaders now prefer female teachers to be leaders in schools. Even so, good women's leadership competencies still experience obstacles to achieving the school's vision, such as; 1) Limited input of quality female human resources, 2) The inability of female leaders to condition their emotions when faced with the natural nature of women (during menstruation, pregnancy, and their obligations as wives and mothers), 3) work piling up, and 4) differences in perceptions between teachers Woman. However, these inhibiting factors can sometimes be countered by factors that support women's leadership, such as; 1) a supportive work environment, 2) a history of education that is linear with work, 3) adequate facilities and infrastructure, and 4) school regulations that support the concept of gender equality. The findings of this study refute previous opinions which stated that Islam is a religion that prohibits women from becoming leaders, but instead, this study provides new evidence that Islam is a religion that upholds the concept of gender equality.